The walkaway shoes and other stories - Blyton, Enid (Award London, 1998)
The Walkaway Shoes and Other Stories is a collection of short stories by Pauline Clarke. The stories explore various aspects of human nature, relationships, and personal growth. In the title story, "The Walkaway Shoes," a young protagonist discovers a pair of magical shoes that grant her the freedom to escape mundane situations, prompting reflections on independence and responsibility. Other stories in the collection follow characters facing dilemmas of friendship, courage, and decision-making, each with a touch of whimsy and fantasy. The themes of self-discovery and moral choices run throughout the book.